Post-Soviet School Education Policy in Georgia - Darchashvili, Manana (Journal of Education Culture and Society, 2023)
Aim. The purpose of the work is to find, study, thematically, chronologically present, and analyse the place of education and especially school education in Georgian politics in the post-Soviet period in Georgia, as well as to determine the attitude to the issue, highlight the ongoing activities, and show the existing results and future perspective. Methods. The work is presented based on several researched-studied official government documents, empirical materials, analysis of scientific research papers, and the use of the comparative method in the Georgian reality of the post-Soviet period. Results. The paper identifies the current situation at the level of public education in Georgia following the goals of modern-sustainable development since the 1990s, which is known as the most difficult period of Georgia’s history; it highlights the existing legal framework in the school education system and the implementation of the set plans; it shows effective steps of the state to develop and implement education policy. Conclusion. By studying a number of materials, it is confirmed that the political course of Georgia for the promotion of school education in Georgian reality, despite the existing difficult political situation, was characterised by great support when all political teams were in power because the mentioned issue is a part of the domestic policy in the country, which is always important and relevant.